3个回答
展开全部
∫dx/[x+√(1-x^2)]
令x=sint
原式=∫cost/(sint+cost) dt
=1/2 ∫(cost-sint)/(sint+cost) dt+1/2 ∫(cost+sint)/(sint+cost) dt
=1/2∫1/(sint+cost) d(sint+cost)+1/2∫dt
=1/2ln|sint+cost|+1/2t+c
t=arcsinx
cost=√1-x^2
所以
原式=1/2ln|x+√(1-x^2)|+1/2arcsinx+C
令x=sint
原式=∫cost/(sint+cost) dt
=1/2 ∫(cost-sint)/(sint+cost) dt+1/2 ∫(cost+sint)/(sint+cost) dt
=1/2∫1/(sint+cost) d(sint+cost)+1/2∫dt
=1/2ln|sint+cost|+1/2t+c
t=arcsinx
cost=√1-x^2
所以
原式=1/2ln|x+√(1-x^2)|+1/2arcsinx+C
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询